1993
DOI: 10.1016/0278-6125(93)90012-i
|View full text |Cite
|
Sign up to set email alerts
|

Review of research in feature-based design

Abstract: Research in feature-based design is reviewed. Feature-based design is regarded as a key factor towards CAD/CAPP integration from a process planning point of view. From a design point of view, featurebased design offers possibilities for supporting the design process better than current CAD systems do. The evolution of feature definitions is briefly discussed. Features and their role in the design process and as representatives of design-objects and design-object knowledge are discussed. The main research issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0
7

Year Published

1995
1995
2004
2004

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(82 citation statements)
references
References 44 publications
0
75
0
7
Order By: Relevance
“…They are initially modeled based on machining features that can be used to integrate CAPP and CAM packages [11]. After many years of development on feature-based design or manufacturing, most of the implemented features are still CAD application oriented and related to machining processes (e.g.…”
Section: Feature Technology Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They are initially modeled based on machining features that can be used to integrate CAPP and CAM packages [11]. After many years of development on feature-based design or manufacturing, most of the implemented features are still CAD application oriented and related to machining processes (e.g.…”
Section: Feature Technology Reviewmentioning
confidence: 99%
“…One way to bridge these gaps is to build high-level design expertise and rules in a knowledge-oriented system [9,10] while low-level design intent into a CAD system in the form of information-rich objects, which can be referred to as features in general although there have been many different definitions in the past literature [11][12][13][14]. As shown above, with certain naming conventions, such objects can then be mapped as arguments of predicate calculus, and manipulated with artificial intelligence (AI) languages, such as Prolog.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that modelling of component characteristics and processing system capabilities provides a good basis for solving many of the tasks involved in process planning, appropriate framework and linking the plans to a machining strategy and machine}shop scheduling/loading system. Salomons, Houten and Kals (1993) explain that a feature taxonomy is the structured way in which it classi"es features. A feature subclass can inherit some properties from a super class without a repeated properties declaration.…”
Section: Introductionmentioning
confidence: 99%
“…A good review of research work done in feature-based design is given in Salomons et al (1993). The limitation of the feature-based design approach is that the designer must know in advance what process is to be used to manufacture the part.…”
Section: Introductionmentioning
confidence: 99%